Effects of amitriptyline on oxidative stress parameters in brain tissue of zebrafish, Danio rerio - (:unkn) unknown (Parlar Scientific Publications, 2020)
Amitriptyline (AMI) is one of the commonly prescribed tricyclic antidepressants that to the treatments for major depression, neuropathic ache, migraine and inflammatory diseases which known as inhibitors of serotonin and noradrenaline reuptake. The aim of our study compared to research the dose and time dependent impacts of daily intake doses of AMI, which adapted from human proportionally to weight of zebrafish (Danio rerio). In recent years, because zebrafish genes have high homology with human genes, it is preferred as a model of organism in many drug researches. Initially, fishes were separated into four groups except control group. After, the daily minimum and maximum dose of AMI used in humans were applied to fish during four and thirty days. The levels of catalase (CAT), acetylcholinesterase (AChE), glutathione (GSH), malondialdehyde (MDA) and total protein (TP) were determined by spectrophotometric methods in biochemical analyses. Our results for four and thirty days show that CAT activity was markedly reduced compared with the control group, whereas activity of AChE and levels of MDA were significantly increased by applied maximum AMI concentrations. In aggregate, our results show that decrease in CAT activity and increase in MDA level may cause oxidative stress. For more comprehensive findings further new studies are needed. © 2020 Parlar Scientific Publications. All rights reserved.
Keywords: Amitriptyline; Antioxidative enzyme activity; MDA; Oxidative stress; Zebrafish